2020
DOI: 10.1371/journal.pone.0239531
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory-based study examining the properties of silk fabric to evaluate its potential as a protective barrier for personal protective equipment and as a functional material for face coverings during the COVID-19 pandemic

Abstract: The worldwide shortage of single-use N95 respirators and surgical masks due to the COVID-19 pandemic has forced many health care personnel to use their existing equipment for as long as possible. In many cases, workers cover respirators with available masks in an attempt to extend their effectiveness against the virus. Due to low mask supplies, many people instead are using face coverings improvised from common fabrics. Our goal was to determine what fabrics would be most effective in both practices. Under lab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
0
28
0
2
Order By: Relevance
“…During the use of masks, air passes through a narrow passage and breathing pressure, breathing resistance and breathing quality are affected [ 14 ]. Therefore, besides the filtration capacity, the breathability of the masks is also crucial [ 15 ]. It has been suggested that breathability will not be altered if the flow rate of the air passing through the mask is above 85 L/min [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the use of masks, air passes through a narrow passage and breathing pressure, breathing resistance and breathing quality are affected [ 14 ]. Therefore, besides the filtration capacity, the breathability of the masks is also crucial [ 15 ]. It has been suggested that breathability will not be altered if the flow rate of the air passing through the mask is above 85 L/min [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Silk, like an FFP2 respirator, has properties that may provide a protective barrier against respiratory infection particles such as SARS-CoV-2, but its effectiveness for the respective function remains to be evaluated. [ 46 ] Dentists are the health professionals most at risk for exposure to respiratory infections, and a fabric mask would not provide the necessary protection in a clinical setting. [ 45 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…O uso de EPIs, desinfetantes e sanitizantes é de fundamental importância no combate à Covid-19 (PARLIN, 2020). Contudo, os profissionais da saúde, constantemente expostos a isso em sua prática assistencial, podem desenvolver lesões dermatológicas importantes (SALOMÉ e PONTES, 2020).…”
Section: Discussionunclassified